FABRIC SELECTION FOR WORK WEAR DURING PROCUREMENT PROCEDURE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Nowadays, more and more importance is given to labour protection, health and safety. One of the protective means is suitable clothing. Often workwear serves as a uniform, which characterize the position of the worker and represents the organization. Basically, such types of workwear are sewn or purchased using the procurement procedure. Usually procurement procedure is carried out for the entire sewn product as a whole. When workwear is worked out great importance should be paid to basic fabrics and their protective quality. In order to provide the most suitable choice of the fabric, the procurement procedure of it should be done separately from the sewing service purchase. Fabric production and garment sewing in most cases take place at different companies. In this case, does not always match the probability that the best sewing service provider will offer the best quality fabrics.Technical specification of fabrics should be worked out very carefully. It should include fabric fibre content, structure characteristics, type of finishing, mechanical and physical properties. Fabrics supplier selection can be made after the applicant submitted fabric technical description, were specifies all nominal values of requested technical characteristics. The procurement procedure must include testing of actual characteristics and its comparison with nominal values.Field uniform fabrics are analysed as an example in scientific study. The procurement procedure of these fabrics should be especially accurate. During procurement procedure is important to check conformity of supplied fabric directly to offered characteristics.